Various Myths in Minangkabau Culture: The Impact of Religious Rituals for Millennial Generation in West Sumatera - Muhammad Hanif; Suci Ramadhanti Febriani; Kddour Guettaoui Bedra (Khatulistiwa, 2022)
This study aims to analyze the mythical phenomenon in Minangkabau Culture towards the religious rituals of the Millennial generation in West Sumatera. The method used is based on mix method research; first, researchers identify quantitatively to examine the impact of mythical truth from the perspective of the millennial generation; second, the researchers adopted a qualitative method to identify the response and impact of myths on the religious rituals of the Millennial generation. Researchers used a random sampling technique with 107 respondents. This study identified that 77 people admitted that there were myths that developed in the Minangkabau community and 30 people admitted that they were not aware of the existence of myths. The findings of this study showed the millennial generation in particular does not believe in myths, it only leads to the preservation of education of local cultural values. This research is limited to the sample and research methods used, so that further research is needed regarding the social and religious impacts when myths become the basis of people's lives.